Conocimiento, economía y sociedad en México: un difícil maridaje - Dautrey, Philippe (Diálogos Latinoamericanos, 2019)
Knowledge has resulted to be the main production input in the developed countries. At the same time, communication and information technologies have made its diffusion wider. However, in Mexico the knowledge economy is reduced owing to an adverse development model and a cognitive gap. As for the knowledge society, in which mass media plays a leading role, it rather generates an information overload. In conclusion, knowledge – or, on the contrary, knowledge gap – production refers to the context of both economy and society. This is the perspective that is being analyzed in this paper, in reference to Mexico. In other words, it comes down to understanding how unfavourable industrial specialisation, neoliberal ideology supremacy and corporatist institutions shape cognitive capitalism.